Proteinase-activated receptor 2 distribution and expression in equine small intestine tracts following herniation through the epiploic foramen. (August 2019) - Romagnoli, Noemi; Zannoni, Augusta; Bernardini, Chiara; Gobbetti, Thomas; Bombardi, Cristiano; Rambaldi, Anna Maria; Morini, Maria; Dondi, Francesco; Rinnovati, Riccardo; Lambertini, Carlotta; Spadari, Alessandro
Abstract: Proteinase-activated receptor 2 (PAR2 ) is a G-protein-coupled receptor for trypsin and mast cell tryptase; it is highly expressed at the intestinal level with multiple functions, such as epithelial permeability and intestinal motility. The aim of the study was to evaluate the distribution and expression of proteinase-activated receptor 2 in the small intestine during herniation through epiploic foramen. In this prospective clinical study, eight horses admitted for colic and which underwent exploratory laparotomy were considered. During surgery, the jejunum or the ileum was sampled by enterectomy. Morphological examination (histology, PAR2 immunohistochemistry) and molecular biology analysis (western blot and quantitative polymerase chain reaction) were carried out on the resected intestinal samples. The Marginal Injured Tracts (MITs) and Central Injury Tracts (CITs) were defined as the oral and caudal marginal segments of the resected bowel tract and as the geometric centre of the intestinal ischaemic lesion length, respectively. The PAR2 immunoreactivity was particularly evident in the epithelial cells, with higher immunoreactivity in the MIT rather than in the CIT. Moreover, a different immune localisation was observed in the MITs at the cell membrane level and in the CITs in the cytoplasm. No statistical difference was observed in PAR2 mRNA and protein (44 kDa) expression between the MIT and the CIT. The PAR2 protein content in the intestinal tracts which were removed from horses with herniation was lower when compared with the control animals. This study provided data concerning the PAR2 presence and distribution in horses with intestinal herniation through the epiploic foramen. Highlights: Colic is a frequent emergency in equine medicine that is associated with severe gastrointestinal diseases. The protein activated receptor-2 (PAR2 ) is involved in the pathogenesis of inflammation in the gastrointestinal tract. The PAR2 is expressed in the small intestine of healthy and pathological horses. The PAR2 has been activated during ischemic lesions due to herniation through the epiploic foramen.